Model Pengendalian Resiko Stunting pada Remaja dalam Program Makanan Bergizi Gratis di Provinsi Jawa Timur - Arief, Ria Qadariah; Widayanti, Linda Prasetyaning (State Islamic University of Sunan Ampel, 2026)
Adolescent stunting remains a significant public health challenge in Indonesia, with a prevalence of 19.8% in East Java Province. The Free Nutrition Food Program (MBG) aimed to address this issue, but its effectiveness depends on multiple interrelated factors. This study aimed to develop a risk control model for adolescent stunting within the framework of the MBG Programme across various locations in East Java. This sequential embedded mixed‑methods study involved 278 adolescents aged 16–18 years from several schools across multiple areas in East Java, including Bangkalan, Mojokerto, and other districts, between July and October 2025. Quantitative data were collected through structured online questionnaires distributed digitally, as well as direct anthropometric measurements (height and weight) performed by trained enumerators at each school. Qualitative data were obtained through online and offline in‑depth interviews with teachers and parents. Multivariate logistic regression analysis was performed to identify determinants of stunting status. Thematic analysis was used for qualitative data. The results prevalence of stunting was 19.4%. The strongest determinant was government assistance (OR=21.2; 95% CI:15.3–27.2), followed by sleep adequacy (OR=13.4; 95% CI:12.7–14.1), physical activity (OR=13.1; 95% CI:12.0–14.2), meal frequency (OR=8.9; 95% CI:8.6–9.3), breakfast habit (OR=8.4; 95% CI:7.9–8.9), portion adequacy (OR=6.8; 95% CI:6.5–7.1), taste preference (OR=6.7; 95% CI:6.4–7.1), and nutritional content perception (OR=4.4; 95% CI:4.2–4.6). The final model explained 68.4% of the variance in stunting (Nagelkerke R²=0.684) with excellent discriminatory power (AUC=0.892). Qualitative findings highlighted the importance of distribution consistency, adaptation to school schedules, and the synergistic effect between MBG and social protection programmes, which varied across regions. The MBG programme shows significant potential when implemented with an integrated approach addressing socioeconomic factors, behavioural factors (sleep and physical activity), and programme quality (portion and taste). The developed risk control model provides an evidence‑based framework for interventions to reduce adolescent stunting prevalence across various regions in East Java and similar settings.